2021
DOI: 10.1002/mop.33044
|View full text |Cite
|
Sign up to set email alerts
|

An in‐band full‐duplex antenna for dual‐band application

Abstract: A dual‐band, dual‐polarized in‐band full‐duplex antenna with good isolation performance is presented for wireless local area network (WLAN) applications. A neutralization line is connected between the grounds of the transmitter (Tx) and receiver (Rx) antennas to enhance the isolation. Further enhancement in isolation is achieved by using a 180° ring hybrid coupler between receiving antenna elements. Here the dual‐band monopole antennas are used as transmitting and receiving antenna elements. For better isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this scheme, a reflective terminal is used to cancel the direct coupling between the transmit and receive antenna. Whereas by employing differential feeding schemes and/or 180 °hybrid couplers for patch antenna, interport isolation ranging from 40 to 90 dB can be achieved [4][5][6][7][8]. However, it can be observed that high levels of isolation are achieved at the cost of bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…In this scheme, a reflective terminal is used to cancel the direct coupling between the transmit and receive antenna. Whereas by employing differential feeding schemes and/or 180 °hybrid couplers for patch antenna, interport isolation ranging from 40 to 90 dB can be achieved [4][5][6][7][8]. However, it can be observed that high levels of isolation are achieved at the cost of bandwidth.…”
Section: Introductionmentioning
confidence: 99%